Design Microstrip Antenna for 6G Application using CST Microwave Studio - Halid, Siti Mariam; Kamarudin, Muhammad Ramlee (Evolution in Electrical and Electronic Engineering, 2022)
This research focus on designing Microstrip Patch Antenna for a 6G Application. In the sphere of mobile communication, the rate of scientific and technological advancement has never diminished. 6G were introduced to provide customers with high bit rates, low latency, large capacity, as well as a variety of new services and vertical applications. This research aims for an antenna that works on 300GHz where the performance of the antenna was studied and the improvement of the antenna were applied. Hence in this research, an antenna with 300GHz resonant frequency has been designed in CST Microwave Studio. Few designs were done and analyzed. In addition, arrays were introduced where it helps to improve the performances and the arrangement of the array were justified. In this research it will shows Voltage Standing Wave Ratio (VSWR) and also the gain of the antenna, with or without arrays. With addition of arrays, it is proven that the performance of the antenna was increase where it has higher value of gain shown in the results. The overall simulation results showed promising output that can be implemented by others who wanted to develop the actual hardware of the antenna.